Determinan Corporate Sustainability Performance Dengan Auditor Internal Sebagai Pemoderasi - Djali, Hartina; Djaddang, Syahril; Merawati, Endang Etty (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2023)
Corporate Sustainability Performance is linked to the company's business strategy, which aims to benefit stakeholders while improving people's lives and protecting the environment.This study aims to examine the effect of Intellectual Capital and Free Cash Flow on Corporate Sustainability Performance with the Internal Auditor as moderating. Intellectual Capital is proxied by Human Capital Efficiency, Structural Capital Efficiency and Capital Employed Efficiency. Meanwhile, Corporate Sustainability Performance is proxied by the CSR index which is based on the 2016 Global Reporting Initiative Standard. The population of this study are companies included in the LQ45 Index during the 2017-2021 period. The sample was selected using purposive sampling method and 20 companies were selected as the research sample. Data analysis using Structural Equiation Model using WARP PLS version 7.0 application. The results of this study indicate that Human Capital, Structural Capital and Employed have no significant effect on the Company's Sustainability Performance. Meanwhile, Free Cash Flow has a significant positive effect on the Company's Sustainability Performance. Internal auditors can weaken the relationship between Human Capital and Corporate Sustainability Performance, the relationship between Structural Capital and Corporate Sustainability Performance and the relationship between Free Cash Flow and Corporate Sustainability Performance. Meanwhile, the Internal Auditor can strengthen the relationship between Capital Employed Efficiency and Corporate Sustainability Performance. The results of this study have an impact on company management to consider the company and as information for investors in determining investment decisions.